Sensitive to music? Examining the crossmodal effect of audition on sweet taste sensitivity - Guedes, David; Prada, Marília; Garrido, Margarida V.; Caeiro, Inês; Simões, Carla; Lamy, Elsa (Food research international, 2023)
[Display omitted] •The influence of music on taste sensitivity was examined.•A “high sweetness” soundtrack led to higher sweet taste recognition at near-threshold.•No overall differences were observed in detection and recognition thresholds.•The crossmodal influence of music depends on the parameter of taste function. Previous research has shown that music can influence taste perception. While most studies to date have focused on taste intensity ratings, less is known about the influence of musical stimuli on other parameters of taste function. In this within-subjects experiment (N = 73), we tested the effects of three sound conditions (High Sweetness soundtrack – HS; Low Sweetness soundtrack – LS; and Silence – S) on sweet taste sensitivity, namely, detection and recognition. Each participant tasted nine samples of sucrose solutions (from 0 g/L to 20 g/L) under each of the three sound conditions in counterbalanced order. We assessed the lower concentrations at which participants were able to detect (detection threshold) and correctly identify (recognition threshold) a taste sensation. Additionally, the intensity and hedonic ratings of samples above the recognition threshold (7.20 g/L) were analyzed. Affective variations (valence and arousal) in response to the sound conditions were also assessed. Although music did not lead to significant differences in mean detection and recognition thresholds, a larger proportion of sweet taste recognitions was observed at a near-threshold level (2.59 g/L) in the HS condition. The intensity and hedonic ratings of supra-threshold conditions were unaffected by the music condition. Significant differences in self-reported mood in response to the sound conditions were also observed. The present study suggests that the influence of music on the sweet taste perception of basic solutions may depend on the parameter under consideration.